Rapid Multiplication of Averrhoa carambola through in vitro culture (Journal of Bio-Science, 2009)
Averrhoa carambola L. (Family - Oxalidaceae) is a tropical common evergreen woody fruit plant. It has many commercially exploitable and beneficial attributes. The plant is a native to the south East Asia and presently being grown as a garden tree in all tropical and subtropical countries (Tidbury 1976). The fleshy sweet and sour fruits are widely eaten in Bangladesh. Carambola fruits are rich in reducing sugar, minerals and vitamin C and A (Ghose and Dhua 1990). Carambola is propagated by seeds. Cutting budding and grafting are unsuccessful. Characters of seed propagated plants vary widely among individuals. Micropropagation method is specifically applicable to species in which clonal propagation is needed (Gamborg and Phillips 1995). Rapid clonal propagation of desired genotype is one of many applications of plant tissue culture. Regeneration of plants in vitro from somatic tissue of Averrhoa carambola was first attempted by Litz and Conover (1980). This report was not satisfactory in multiplication rate and establishment of regenerated plantlets in soil. The objective of this paper is to establish an efficient and reproducible method for rapid clonal propagation of Averrhora carambola from aseptically grown seedlings. doi: 10.3329/jbs.v15i0.2161 Â  J. bio-sci. 15: 175-179, 2007